Strengthening Performance and Strategic Management in Public Sector Organizations: A Case Study of Performance of Government Agencies in Sumedang District - Sundawa Bahtiar (Budapest International Research and Critics University, 2022)
Strategic management can be understood as more than just making and implementing strategic plans, but in a broader scope this function is a continuous process that includes all activities carried out to make plans, actions, and policies to achieve organizational goals or missions. Public sector organizations as public service providers in Indonesia, are very responsible for being able to provide the best service in order to create prosperity for the wider community, of course, through an appropriate organizational strategy, the implementation of the vision and mission as well as the goals of the organization's institutions can be managed and applied to the community. very long period of time. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the implementation of strategy in an organization is closely related to several important aspects such as the scope of organizational activities, allocation and reallocation of key resources within the organization, values, expectations and goals. and the implications of operational change across the organization. So that it can be said that organizational strategic management is a process that in each stage requires participation from all parties, and the responsibility of the leader as a determinant of policy direction in establishing a framework for carrying out these various processes in a relevant and accurate manner. Government Agency Performance Reports as one of the media to provide information about performance achievement. Information on government agency performance accountability is needed by the government because based on this information, the government has decision-making material to make management improvements in the administration of government affairs that are even better in the future. .